Therapeutic Effects of Medicinal Plants on Diabetic Foot Ulcers: A Systematic Review - Efa Refiani; Rita Maliza; Husna Fitri; Putri Lestari (Journal of Agromedicine and Medical Sciences, 2021)
Diabetic Foot Pain and Ulcers is one of the complications diseases caused by Diabetes Mellitus (DM). Based on data from the Ministry of Health in 2014, diabetic foot ulcers in Indonesia 54%. Diabetic foot ulcer disease can cause infection and tissue death. Treatment of diabetic foot ulcers has been treated with ointments or gels containing antimicrobials, biomaterials, and active compounds, accelerating the wound healing process. The active compounds from medicinal plants that play a role in the treatment of diabetic foot ulcers have been widely reported. The purpose of writing this article is to look at the therapeutic effects of active compounds that play a role in wound healing. In this systematic review, we searched the PubMed, Science Direct, and Google Scholar databases to identify primer articles that were published from 2010 to 2020. Ten studies were selected and published between 2015-2020. Furthermore, the plant species used for the treatment of diabetic foot ulcers contain active phenolic, gallic acid, flavonoids, gallic acid, flavonoids, and tannins compounds that play a role in the acceleration of the healing process of diabetic foot ulcers. Keywords: Diabetes mellitus, diabetic foot ulcers, the active compound, medicinal plants